PENGEMBANGAN FORMULA ENTERAL PUTELA BERBASIS PUTIH TELUR (Albumen) DAN TEPUNG LABU KUNING (Curcubita Moschata) UNTUK PENDERITA DIABETES MELITUS - Fattonah, Anissa; Isdiany, Nitta (Poltekkes Kemenkes Bandung, 2023)
This study aims to determine the effect of differences in egg white flour and pumpkin flour formulations on the quality of high-protein and high-fiber enteral food for Diabetes mellitus patients